Teachers’ perception towards total quality management practices in Malaysian Higher Learning Institutions - Haque, A. K. M. Ahasanul; Sarwar, Abdullah Al-Mamun; Yasmin, Farzana (Scientific Research Publishing, 2013)
The service industry is a rapidly changing industry and this dynamic culture offers a challenge for the service companies to lead or to actually survive in this competitive environment. As the education indus-try is a part of the overall service industry, this raises the need for a solid base to be developed to reach for high quality service in the education industry. Though, adoption of TQM in the higher educational institu-tions is of common practice in the Western world, however, the history of TQM adoption in the Malay-sian higher educational institutions is not very long. Therefore, the main purpose of this study was to identify the factors influencing the level of TQM practices in the Malaysian higher learning institutions based on the teacher’s perceptions. In doing so, this study was conducted in both types of Malaysian higher educational institutions (public and private). Total 300 questionnaires were distributed randomly, out of which 206 were returned. After collecting the data, statistical tests were performed using SPSS and Amos. This study has got satisfactory results. Results also show identical results with the previous studies. However, this study has pointed out that there is still room for improvement that affecting the level of TQM practices in the Malaysian educational institutions. Finally, future directions are provided at the end of the paper.